Training intensity evaluation in “Long Rope” horses – Brazilian Western Modality (Research, Society and Development, 2020)
The present study aimed to evaluate the training intensity of horses in the team roping through serum lactate and glucose concentrations. For this purpose, nine American Quarter horses, clinically healthy, male and female, aged between 3 and 15 years, were used. The animals were divided into three groups according to the number of lasso throwings in the training; group one (G1) three throwings, group two (G2) five throwings, group three (G3) with seven throwings. Two blood samples were obtained, one at rest and the other right after the activity required. The results indicated that lactate concentrations presented a significant increase at all times in comparison to the average at rest, however they remained within the value of reference of the species, demonstrating that all the animals were able to perform the proposed strain. Glucose values showed a significant increase in time 1 when comparing with time zero in all groups, apart from group 1 when using the portable glucometer. Therefore, it is suggested to give preference to the analysis performed by biochemical devices to measure the equine blood glucose in equestrian tests. Furthermore, it is concluded that the physical effort imposed for these horses up to seven lasso throwings in the Team Roping test was compatible with their conditioning.